Sacra Scripta. Journal of the Centre for Biblical Studies. - Comşa, Sorina-Cătălina (Caietele Echinox, 2013)
The article reviews the January 2011 issue of the periodical "Sacra Scripta: Journal of the Centre for Biblical Studies," Year IX.